PENGEMBANGAN SEDIAAN BODY LOTION EKSTRAK ETANOL BUNGA TELANG (Clitoria ternatea L.) - Sugiharta, Sudrajat; Septiani, Putri; Fikayuniar, Lia (Jurnal Buana Farma, 2024)
An alternative to synthetic ingredients with a focus on reducing the sticky effect upon application. Given the belief in natural ingredients being safer than synthetic chemicals, this body lotion was designed to utilise the antioxidant potential of telang flower. This study aims to develop a body lotion based on telang flower extract (Clitoria ternatea L.). This study used a quasi-experimental laboratory method with a completely randomised design (CRD) with a 3 x 2 factorial pattern, testing variations in the concentration of stearic acid (2.5%, 5.0%, 7.5%) and liquid paraffin (5.0%, 15%) on the quality of the Body lotion formulation. Organoleptic test results showed that all Body lotion formulas had a characteristic aroma and colour of bay flower, with varying colours depending on the concentration of ingredients. Homogeneity test showed that all formulas were homogeneous without coarse particles. The pH, viscosity, adhesion, and spreadability parameters of the Body lotion met the requirements of good cosmetics, with pH values between 6.68-7.47, viscosity between 2033-2459 cps, adhesion between 22-43 seconds, and spreadability between 5-6.9 cm. The acceptability test showed that all panelists liked the colour, aroma, and texture of the body lotion, and did not feel the sticky effect after application. This study concludes that variations in the concentration of stearic acid and liquid paraffin affect the quality of Body lotion, with the optimal formulation being able to reduce the sticky effect and increase the comfort of use on the skin.